2011
DOI: 10.1002/ibd.21507
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis resistance of mucosal lymphocytes and IL-10 deficiency in patients with steroid-refractory Crohnʼs disease

Abstract: Apoptosis resistance of mucosal T and B cells in steroid-refractory and -dependent CD patients appears during the evolution of the acute phase, limiting its clinical application as a predictor marker. In contrast, increased expression of IL-10 at an early stage of active steroid-sensitive CD patients supports its usefulness at predicting a good steroid response. Steroid-dependent and -refractory CD patients share similar molecular and cellular pathophysiological mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
15
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 36 publications
4
15
0
Order By: Relevance
“…Although there was low transcriptional expression of Bcl2 in the ICD group, no differences were observed with regard to Bcl-2 protein expression, as analyzed by immunohistochemistry in this group. These findings reinforce the data of Itoh et al [10] and Santaolalla et al [17], who associated the defective apoptosis in the lamina propria to the Bax-related pathways.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Although there was low transcriptional expression of Bcl2 in the ICD group, no differences were observed with regard to Bcl-2 protein expression, as analyzed by immunohistochemistry in this group. These findings reinforce the data of Itoh et al [10] and Santaolalla et al [17], who associated the defective apoptosis in the lamina propria to the Bax-related pathways.…”
Section: Discussionsupporting
confidence: 91%
“…In this situation, the remaining cells may be the ones that show low rate of apoptosis and high rate of proliferation in order to recover the affected area and restore function. Concerning the decreased apoptosis in lamina propria cells of CD compared to the controls, and the fact that part of these cells are immune cells, this confirms previous published results in the literature [10], [17].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Although IRF-1 Ϫ/Ϫ and IL-10 Ϫ/Ϫ mice are more susceptible to DSS-induced colitis [38,55], IRF-1 signaling and IL-10 were found to be dispensable for APP-mediated protection. The finding that APP can confer protection against colitis in the absence of IL-10 is particularly intriguing, as patients with severe Crohn's disease are defective in IL-10 production [56], and IL-10 expression is impaired in the intestinal mucosa of Crohn's disease patients who failed to respond to steroid therapy [57]. Thus, APP uses an IL-10-independent pathway to provide protection against IBD, implicating APP as a potential benefit to complement therapies targeting IL-10, which can be ineffective.…”
Section: Discussionmentioning
confidence: 97%
“…However, the colonic IL-10 expression profile in patients with IBD is controversial. Most reports indicate that mucosal levels of IL-10 are increased in UC[27,35], but normal[28], decreased[36,37] and elevated[38,39] mucosal IL-10 levels are reported for CD. Recent studies have demonstrated that polymorphisms of the IL-10 gene are correlated with the development of UC and CD[40].…”
Section: Discussionmentioning
confidence: 99%